Malia Berry: capstone - Berry, Malia, artist (Colorado State University. Libraries, 2023)
The artist's statement: Hello! My name is Malia Berry and I am an illustrator, character artist, and graphic designer. I work both digitally and traditionally in a variety of styles, using most frequently Photoshop, Illustrator, watercolor, and india ink to create my pieces, though I love experimenting with other media as well, such as animation, oil and acrylic paints. I draw inspiration from my other interests relating to pop-culture, such as novels, manga, comics, anime, movies, animated films, and especially video games. All of these influence the subjects, themes, and look of my art and characters, showing up in the form of whimsical, fantasy imagery. I believe that art should be flexible, and to limit myself to one theme or subject would be to limit my self-expression. Therefore, the themes in my body of work vary greatly; I touch on both darker and lighter subjects, including topics of mental health, and negative emotions, but use more whimsical imagery to create lighthearted, cartoon-like illustrations and stories.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design